PERUBAHAN PERILAKU KONSUMSI PADA MASYARAKAT JAWA TIMUR SELAMA MASA PANDEMI COVID-19 - Arina Sofi Ulya; Dwi Budi Santoso (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The COVID-19 pandemic that occurred in various countries affected almost all aspects of life, one of which was community activities. The existence of social restriction policies has a direct impact on the decline of economic activity, which has the opportunity to change people's consumption behavior. Consumption behavior is the activity of spending income to maximize utility. This study aims to determine changes in consumption behavior in the people of East Java during the COVID-19 pandemic. The method used is a classy typology model to see changes in consumption in 2019 and 2020. Then, it was analyzed using the COVID-19 risk index in each region. The results showed that the changes in consumption that occurred in East Java were influenced by the COVID-19 risk index, areas that have a high risk index tend to experience changes in consumption and vice versa. The changes in behavior that occur due to covid-19 risk factors vary in each region so that changes occur in the proportion of consumption of goods/services and changes in savings rates. This research can assist the government in taking economic recovery policies after the COVID-19 pandemic in each region by looking at the COVID-19 risk index.